2008
DOI: 10.1108/09513540810861856
|View full text |Cite
|
Sign up to set email alerts
|

A study of leadership effectiveness in a large VET institution in Australia

Abstract: Purpose -This paper aims to focus on a study of the effectiveness of head teacher leadership within TAFE NSW. Design/methodology/approach -Quantitative and qualitative methods were employed to identify and measure the effective leadership attributes of the head teachers. The research sample consisted of head teachers and teachers. Findings -The results suggest that the effectiveness of head teachers' leadership needs to be improved substantially. More specifically, there was a significant difference between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 16 publications
1
20
0
1
Order By: Relevance
“…Factors that affect the development of teacher leadership include school principals supporting the staff in different aspects (Hart, 1994;York-Barr & Duke, 2004;Wenner & Campbell, 2016), giving teachers time to develop themselves (Chew & Andrews, 2010), the existence of learning communities in schools that ensure professional collaboration (Hunzicker, 2012;Chamberland, 2009), and an environment of trust and peace at school (Beachum & Dentith, 2004;Gordin, 2010;York-Barr & Duke, 2004). However, teachers' lack of time, poor communication, structural factors and personal characteristics (Wenner & Campbell, 2016), lack of shared vision (Brooks, Scribner, & Eferakorho, 2004), excessive workload, insufficient support (Adams & Gamage, 2008), and an authority and autonomy gap (Friedman, 2011) weaken teacher leadership. Consequently, it can be argued that teachers' leadership behaviors increase with the levels of schools regarding task-oriented, support-oriented, bureaucratic, and success-oriented culture.…”
Section: Discussion Results and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that affect the development of teacher leadership include school principals supporting the staff in different aspects (Hart, 1994;York-Barr & Duke, 2004;Wenner & Campbell, 2016), giving teachers time to develop themselves (Chew & Andrews, 2010), the existence of learning communities in schools that ensure professional collaboration (Hunzicker, 2012;Chamberland, 2009), and an environment of trust and peace at school (Beachum & Dentith, 2004;Gordin, 2010;York-Barr & Duke, 2004). However, teachers' lack of time, poor communication, structural factors and personal characteristics (Wenner & Campbell, 2016), lack of shared vision (Brooks, Scribner, & Eferakorho, 2004), excessive workload, insufficient support (Adams & Gamage, 2008), and an authority and autonomy gap (Friedman, 2011) weaken teacher leadership. Consequently, it can be argued that teachers' leadership behaviors increase with the levels of schools regarding task-oriented, support-oriented, bureaucratic, and success-oriented culture.…”
Section: Discussion Results and Suggestionsmentioning
confidence: 99%
“…These issues include lack of teachers' time, poor communication, structural factors and personal characteristics (Wenner & Campbell, 2016), heavy workloads and an obstructive work environment (Adams & Gamage, 2008), and an authority and autonomy gap (Friedman, 2011). The lack of a shared vision (Brooks, Scribner, & Eferakorho, 2004), concentrating leadership in a single person (Chew & Andrews, 2010), a lack of trust (Muijs & Harris, 2006), and teachers not being encouraged to engage in different activities may also reduce their levels of performing leadership behaviors (Danielson, 2006).…”
Section: The Relationship Between School Culture and Teacher Leadershipmentioning
confidence: 99%
“…On the other hand, it is stated that a rule-based, hierarchical and challenging school structure is a significant obstacle to professional behaviors (Yirci, 2017). Excessive workload and obstructive working environment (Adams and Gamage, 2008) and the fact that leadership belongs to a single person (Chew and Andrews, 2010) are significant obstacles for teachers to work in a more qualified manner. Therefore, it can be said that the fact that teachers exhibit professional behaviors is associated with a school culture that promotes teacher leadership because cooperation cultures provide collaborative learning, administrator's support encourages teachers to use more original methods, and a supportive working environment can encourage teachers to take more responsibility for student learning.…”
Section: The Relationship Between Teacher Leadership Culture and Teacmentioning
confidence: 99%
“…In fact, much of the literature on leadership in post-secondary contexts draws heavily on business literature, which focuses on overall roles and responsibilities and rarely gives serious consideration to issues of teaching and learning (Basham and Campbell 2010;Crossman and Cameron 2014;Smith 2002). In the context of VPE specifically, Adams and Gamage (2008) identified the need for leaders to focus on the educational dimension of their work and suggested that the shift to managerial responsibilities is having an effect on leaders' abilities to ensure quality educational programming. A recent review of research into leadership in vocational education in Australia, the UK, and the USA highlights important issues that leaders in vocational education face (Crossman and Cameron 2014).…”
Section: Introductionmentioning
confidence: 99%
“…tradesperson, health care technologist, or human resource manager) (Anderson 2008). Typically, the purpose of VPE is understood as both improving the social and economic well-being of individuals as well as serving society by ensuring an educated workforce (Adams and Gamage 2008). To keep fulfilling this dual purpose, leaders and educators in VPE need to keep developing themselves and their practices to meet the needs of their learners and society (Sirk et al 2016).…”
Section: Introductionmentioning
confidence: 99%